Peningkatan Proses dan Hasil Belajar Pendidikan Pancasila Menggunakan Model Discovery Learning di Kelas IV SD IT Insan Mulia Merangin - Elza April Lia; Abdulah; Elvima Nofrianni (Yayasan Al-Afif, 2026)
This study aimed to describe the improvement of the learning process and learning outcomes in Pancasila Education through the implementation of the Discovery Learning model among fourth-grade students at SD IT Insan Mulia Merangin. The study employed a Classroom Action Research design conducted in two cycles. Each cycle involved planning, action, observation, and reflection. The participants were 19 fourth-grade students, consisting of 10 boys and 9 girls, in the first semester of the 2025/2026 academic year. Data were collected through observation, learning achievement tests, and documentation. The achievement test consisted of 15 multiple-choice items and 5 essay questions. Data were analyzed using qualitative and quantitative descriptive techniques with a minimum mastery criterion of 68. The findings showed a consistent improvement in the learning process from Cycle I to Cycle II. Teacher implementation increased from 63% in the first meeting of Cycle I to 85% in the second meeting of Cycle II. Student learning activity increased from 37% to 79%. Classical learning mastery also improved from 63% (12 of 19 students) in Cycle I to 79% (15 of 19 students) in Cycle II. Therefore, the Discovery Learning model was effective in improving both the learning process and Pancasila Education learning outcomes of fourth-grade students at SD IT Insan Mulia Merangin.